2009
DOI: 10.1007/s10549-009-0412-3
|View full text |Cite
|
Sign up to set email alerts
|

MUC1* is a determinant of trastuzumab (Herceptin) resistance in breast cancer cells

Abstract: In the United States, 211,000 women are diagnosed each year with breast cancer. Of the 42,000 breast cancer patients who overexpress the HER2 growth factor receptor, <35% are responsive to treatment with the HER2-disabling antibody, called trastuzumab (Herceptin). Despite those statistics, women diagnosed with breast cancer are now tested to determine how much of this important growth factor receptor is present in their tumor because patients whose treatment includes trastuzumab are three-times more likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 40 publications
(54 reference statements)
3
74
0
Order By: Relevance
“…In addition, some studies found that the molecular mechanisms promoting trastuzumab resistance of gastric cancer cells may include: (1) excessive activation of the downstream PI3K/Akt signaling pathway (Velho et al, 2005) (2) cell surface proteins such as HSP90 (Citri et al, 2004;Lang et al, 2007) and mucins (Price, Schiavi et al, 2002) decrease the interaction between trastuzumab and the HER2 receptor, thereby blocking the inhibitory actions of the drug. However, recent studies have shown upregulation of mucin-1 (MUC1), a protein with growth factor receptor-like activity (Fessler et al, 2009 ), mediated the growth of tumor cells, especially the trastuzumab-resistant HER2-positive breast cancer cells. The relationship between MUC1 in gastric cancer cells and its effect on the resistance is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies found that the molecular mechanisms promoting trastuzumab resistance of gastric cancer cells may include: (1) excessive activation of the downstream PI3K/Akt signaling pathway (Velho et al, 2005) (2) cell surface proteins such as HSP90 (Citri et al, 2004;Lang et al, 2007) and mucins (Price, Schiavi et al, 2002) decrease the interaction between trastuzumab and the HER2 receptor, thereby blocking the inhibitory actions of the drug. However, recent studies have shown upregulation of mucin-1 (MUC1), a protein with growth factor receptor-like activity (Fessler et al, 2009 ), mediated the growth of tumor cells, especially the trastuzumab-resistant HER2-positive breast cancer cells. The relationship between MUC1 in gastric cancer cells and its effect on the resistance is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…MUC1 overexpression correlates with high metastatic potential and poor survival; therefore, MUC1 antigens have been used as clinical markers to monitor disease progression in cancer patients (Kohno et al, 1992;Duffy et al, 2000). In addition, previous studies have shown that MUC1 has a pivotal role in tumor development, growth, invasion (Sachdeva and Mo, 2010), oncogenic cellular signal transduction (Raina et al, 2004;Wei et al, 2006), responses to hypoxia (Mikami et al, 2009) and resistance to anti-cancer reagents (Fessler et al, 2009). However, the significance of high expression of MUC1 in tumor cells remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Sample size was calculated taking into account the ratio of positivity for the N. Bahrami et al markers in the two groups based on primary estimates in similar previous studies [24] as well as using sample size estimation formula considering type one error of 5% and type two error of 20%. The data were analyzed using SPSS version 22.…”
Section: Discussionmentioning
confidence: 99%